2015
DOI: 10.7861/clinmedicine.15-1-40
|View full text |Cite|
|
Sign up to set email alerts
|

UK medical selection: lottery or meritocracy?

Abstract: From senior school through to consultancy, a plethora of assessments shape medical careers. Multiple methods of assessment are used to discriminate between applicants. Medical selection in the UK appears to be moving increasingly towards non-knowledge-based testing at all career stages. We review the evidence for non-knowledge-based tests and discuss their perceived benefi ts. We raise the question: is the current use of non-knowledge-based tests within the UK at risk of undermining more robust measures of med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The correlation between entrance test and study success in this study is disappointingly low, even after correction for the effects of reciprocal suppression and range restriction. This finding is in line with results from similar studies [9], but why is it so? Three factors seem to be important: self-selection into the pool of applicants based on self-appraisal and expectations about the test, reduction of variance in predictor and outcome measures due to a high selection ratio, overshooting test difficulty driven by the need to ever more differentiate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The correlation between entrance test and study success in this study is disappointingly low, even after correction for the effects of reciprocal suppression and range restriction. This finding is in line with results from similar studies [9], but why is it so? Three factors seem to be important: self-selection into the pool of applicants based on self-appraisal and expectations about the test, reduction of variance in predictor and outcome measures due to a high selection ratio, overshooting test difficulty driven by the need to ever more differentiate.…”
Section: Discussionsupporting
confidence: 93%
“…In a critique of UK medical student selection, Harris et al (2015) [9] speak out against the use of tests which neither depend on knowledge, nor seem to have substantial predictive validity, specifically the UKCAT and Situational Judgement Tests (SJTs). Instead, they advocate the development of a standardised, nation-wide science knowledge test used in conjunction with pre-university educational attainment.…”
Section: Introductionmentioning
confidence: 99%
“…The questions raised on the validity of non-academic tests and the fairness of their use in a highstakes evaluation have also not been answered [26]. Harris et al have emphasized the fact that non-academic tests have not shown good validity in predicting academic performance in comparison with traditional academic tests, and that their implementation is not fully warranted by evidence [27]. Students could be coached to give desirable answers to non-academic admission tests, making this a potential barrier to implementing such assessment methods [1].…”
Section: Introductionmentioning
confidence: 99%
“…Further research on the SJT is welcome, but its role in selection remains questionable. Assessing students on unfamiliar situations may result in students choosing actions perceived to be high‐scoring, regardless of how they would behave in reality in that particular situation . Besides, the prospect of a national licensing exam in the UK raises doubts about the continued use of the SJT in its current form…”
mentioning
confidence: 99%